INFORMATION THREATS AND THEIR IMPACT FACTORS IN THE CONTEXT OF GLOBALIZATION - Nishonov Abduvoxid Tursunaliyevich (Bright Mind Publishing, 2025)
This article analyzes various information threats in the context of globalization and highlights the main factors influencing their effectiveness. By examining the accelerated development of modern communication technologies and the expansion of digital infrastructures, the paper identifies how disinformation, cyberattacks, propaganda, and other forms of information aggression can compromise the stability of societies worldwide. With an emphasis on the conceptualization of information threats, this study explores the mechanisms through which these threats are disseminated and leveraged. Drawing upon scholarly sources, the discussion outlines practical strategies for strengthening resilience to information hazards at the individual, institutional, and international levels.
Keywords: Globalization, Information Threats, Disinformation, Cyberattacks, Communication Technologies, Propaganda, Media Literacy, Social Stability, Digital Infrastructure, Resilience.